The Dynamics of Islamic Calligraphy Teaching and Learning in South Sulawesi - Ahmad, Abd. Aziz (Jurnal Pendidikan Islam, 2016)
This is a library research studying data collected from library as well as interviews which were then analysed by means of description, arrangement, and interpretation. The result shows that Islamic calligraphy teaching and learning was introduced at the same time as the arrival of Islam in South Sulawesi in 1600s by three Islamic clerics. Pesantren was the main place for such teaching conducted through traditional method in which teacher exemplified handwritten Islamic calligraphy on board then students reproduced the example on paper. The results were then assessed by the teacher. In several Universities in Makassar, such as at Makassar State University (UNM) and State Islamic University (UIN) Alauddin Makassar, Khat (calligraphy) is taught through lecture, demonstration, and assignment. The teachings are performed in class using some media, such as video recording, audio recording, material from the internet, etc. One of calligraphy course institution in South Sulawesi is Lekfiah which was established in 2002. However, this institution experiences decline since the teachers are not fully engaged in managing the teaching. One type of Islamic calligraphy painting technique can be explained over four steps, 1) making basic pattern in form of infinity line, 2) creating background, 3) adding Islamic calligraphy text, and 4) finishing.